Authentic Assessment of English Language Learners Used in An Indonesia High School - Eryantini, Intan; Hikmat, Mauly Halwat (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
The purpose of this study is to describe (1) the type of assessment used by teachers in assessing student in learning english and (2) the authentic assessment used by teachers in assessing students in learning english. The research method used is qualitative with a descriptive type. The sample technique used is purposive sampling. Two English language teachers in grades ten and eleven at SMA Muhammadiyah Special Program Kottabarat Surakarta are the subjects of this study. Interviews, documentation, and observation are the research methods used. The data analysis techniques used are data collection, data reduction, data presentation and then conclusion drawn. The researcher found that there are 4 types of assessments used by the two teachers, namely 1) formative assessment, namely in the form of assignments and try in tests, 2) summative assessment, namely in the form of midterm exams and final semester exams, 3) formal assessments, 4) informal assessments. The authentic assessment used by both teachers in English learning is an essay or portfolio.